473Preventable pertussis burden in Australia within the first year of life by improving vaccination timeliness. (2nd September 2021) - Jayasundara, Duleepa; Randall, Deborah; Sheridan, Sarah; Sheppeard, Vicky; Liu, Bette; Richmond, Peter; Blyth, Christopher; Wood, James G; Moore, Hanna C; McIntyre, Peter B; Gidding, Heather F
Abstract: Background: Previous Australian studies have shown that on-time Diphtheria-Tetanus-Pertussis (DTP) vaccination coverage is 50-60% in certain subpopulations. We estimated the potentially preventable burden of pertussis if, 1) the full primary course and, 2) each dose was given on-time. Methods: Perinatal, immunisation, pertussis notification, and death data were linked for 1, 412, 984 infants born in two Australian states in 2000-2012. A DTP dose administered >15 days after the recommended age was categorised as delayed. For aim 1, pertussis rates up to 1-year of age were compared in infants with ≥1 dose delayed versus all doses on-time, using Poisson regression methods. For aim 2, the expected number of cases preventable by each dose was calculated as the product of the number of cases observed during the period of delay and (1 – dose-specific vaccine effectiveness). Results: 58% of infants had all primary DTP doses on time. We estimated that 85 (95% CI: 61-109) cases per 100, 000 infants, aged 39-days to 1-year, could have been prevented if all infants had been vaccinated on time; 77% of these infants had received ≥1 DTP dose within the first year of life. Estimated preventable burden attributable to delayed DTP1 (58/100, 000) was higher than for DTP2 (26/100, 000) and DTP3 (15/100, 000). Conclusions and Key messages: Poor vaccine timeliness, especially delayed DTP1, is a key contributor to the residual burden of pertussis. These findings can inform cost-benefit analyses of targeted programs and public health messaging to reduce delays.